Jaciara/MT : do tempo passado da colonização e da usina ao tempo futuro da agricultura moderna e do turismo - Pedroso, Claudia Maria Waechter (2015)
The objective of this study is to extract relevant information to the history and economy the county of Jaciara state of Mato Grosso from the perspective of economic transformations that have occurred over the colonization process of the county that is seen like “Past age”, which was covered by the productive activities of the power plant sugarcane. This power plant, which had influential action in the city’s history and it continues to have direct action on the city until today, thus the city faces difficulties front of financial crises that instigate the entire economic dynamic of Jaciara. Therefore the local population has sought to place on their horizon expectation to “future age” giving opening for tourist and modern agriculture, like alternative economic activities capable of solving the crisis.